Kohtaamisia, katkoksia ja sidoksia tutkimus Supermammojen vertaisryhmän äitityöstä - Eronen, Eija (Tampere University Press, 2017)
"Encounters, breaks and bonds: a study of the mother work in the Supermammat peer group This study explores a peer group for mothers, which is presented by the pseudonym Supermammat. The group is a third sector agent, which has served mothers and their children almost three decades. In the Supermammat group mothers get opportunity for carrying out functional programme, taking their children to organized childcare, sharing peer support and receiving professional aid. In addition to weekly meetings, outings, camps and other recreational activities are organized in the group. The aim of the operation is to support motherhood. The objective of the study is to describe practices of supporting mothers in the operation of the Supermammat group. The objective is approached by treating group's history, current operation and principles directing it together with workers and their job towards supporting mothers participating in the operation of the Supermammat group. However, the study par excellence gives voice to people for whom the group has established. It's most central aim is to tell what kind of meaning the operation of the group has for mothers. This is ethnographically executed case study, which starting point is to explore restricted research subject by utilizing different perspectives and datas. The core data consists of interviews of mothers participated in the operation of the Supermammat group (N=23) and fieldnotes gathered during participant observation. In addition, interviews of persons worked on the group (N=11) are included in the data. The data gathered is supplemented by the documents from the operation of the group. Research findings indicate that the operation of the group has turned more professional and functionally more various in the course of time. The operation consists of many elements, reaches dozens of mothers annually and requires contribution of several agents. Participating in the operation gets it's meaning as encounters, breaks and bonds. The group gives an opportunity for encounters forming both peer support and professional aid. At the same time, it constructs a chance of withdrawing from everyday life by producing breaks to mother's routines. In addition, participating in the operation of the Supermammat group gives space for constructing an affinity, various relationships and connections fastened on the group. "